Founders: Christopher Taylor. (2nd January 2021) - Everson, Paul; Stamper, Paul; Williamson, Tom; Fairclough, Graham
ABSTRACT: 'Founders' is an intermittent series of short, critical appreciations of scholars, researchers and others whose work and ideas, mainly in Britain, have made particularly sweeping, influential and foundational contributions to the development of historically- and archaeologically-informed landscape studies. This latest addition to the series concerns Christopher Taylor, whose death on 28th May 2021 was noted in the Landscapes editorial in issue 21.2.